2007
DOI: 10.1302/0301-620x.89b12.19400
|View full text |Cite
|
Sign up to set email alerts
|

Total hip replacement in renal transplant patients

Abstract: Avascular necrosis of the femoral head creates considerable morbidity in successful renal transplant recipients who are generally young and expect active lifestyles. Total hip replacement is considered the treatment of choice in these patients, but surgeons may be wary because of a supposed increase in the risk of infection and other complications. A review of the literature reveals that cemented hip arthroplasty provides good to excellent functional outcomes for renal transplant patients. Most authors have fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 46 publications
0
53
0
3
Order By: Relevance
“…We did find alcohol abuse was a clear risk factor for infection, but this does not agree with others' findings [37]; this disagreement could be explained by a sociological difference (prevalence of alcohol abuse in population, highly variable among regions and cultures), or by alcohol abuse (immunosuppressant) in the perioperative period (once the patient is outside the hospital). Finally, while some preoperative conditions are not major risk factors in our case-controlled study, contradictory published data include diabetes [17,20], obesity [20,24,33,35], rheumatoid arthritis [5,6,13,46], and immunosuppressants [28,40].…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…We did find alcohol abuse was a clear risk factor for infection, but this does not agree with others' findings [37]; this disagreement could be explained by a sociological difference (prevalence of alcohol abuse in population, highly variable among regions and cultures), or by alcohol abuse (immunosuppressant) in the perioperative period (once the patient is outside the hospital). Finally, while some preoperative conditions are not major risk factors in our case-controlled study, contradictory published data include diabetes [17,20], obesity [20,24,33,35], rheumatoid arthritis [5,6,13,46], and immunosuppressants [28,40].…”
Section: Discussionmentioning
confidence: 60%
“…Moreover, several of those studies are not primarily focused on infection, although they contain information on infected patients [11,13,17,18,24,36,40,45,46]. Finally, the level of evidence in many of them is low; we have found seven case series (Level of Evidence IV) [3,6,13,16,17,21,40,46] and many nonsystematic reviews (Level of Evidence V) [1,18,23,25,28,34,38,45] and expert opinions (Level of Evidence V) [2,4,30]. We believe it important to learn and identify these risk factors in the individual patient for to check for and minimize risk factors or, when not possible to consider specific prophylactic measures.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…[28][29][30] The infection rate for THA in corticosteroid-induced osteonecrosis ranges from 1.3% to 19% in various studies. 8,26,[31][32][33] In the present study, the infection rate was 6%; this only represents 2 hips, and from our small sample size it is difficult to draw any firm conclusions about the incidence of periprosthetic infection in patients with corticosteroid-induced osteonecrosis compared with the general THA population.…”
Section: Limitationsmentioning
confidence: 82%
“…7 However, other authors have reported acceptable results and low failure rates with the use of cementless femoral stems using modern implant designs and post-transplant immunosuppression protocols, despite the previously mentioned risks. 8,9 Given the potential complications previously associated with THA following renal transplantation, it is possible that patients with osteonecrosis using corticosteroids for other indications may also be at risk.…”
mentioning
confidence: 99%